Identification of a transactivating function mapping to the putative immediate-early locus of human herpesvirus 6. - Martin, M E (1991)
Sequencing studies have indicated that the unique component of the human herpesvirus 6 (HHV-6) genome and the unique long segment of the human cytomegalovirus genome are genetically colinear. Of particular interest is the identification of a region of local CpG dinucleotide suppression in the genome of HHV-6, a feature conserved in the genomes of human cytomegalovirus, murine cytomegalovirus, and simian cytomegalovirus, and a characteristic of the major immediate-early loci of these viruses. Adjacent to this region in HHV-6 are approximately 30 copies of a 103- to 108-bp sequence element, which contains consensus binding sites for the transcription factors AP2 and NF kappa B, in addition to a single KpnI recognition site. Together, these KpnI repeat units may compose an immediate-early enhancer, analogous to those found in the cytomegaloviruses. We present the sequence of this region of HHV-6 and demonstrate that a transactivating function is encoded by this region. We have used polymerase chain reaction to synthesize fragments containing open reading frames and 5' sequences with or without the upstream KpnI repeat units. Effector plasmids containing these HHV-6 coding and 5' sequences were able to effect activation of heterologous promoter-chloramphenicol acetyltransferase (CAT) constructs, including adenovirus E3-CAT and E4-CAT, human T-cell lymphotropic virus type I long terminal repeat (LTR)-CAT, and human immunodeficiency virus LTR-CAT, in cotransfection experiments in Vero cells and peripheral blood lymphocytes. Furthermore, we have identified the major open reading frame (RF4; 2.3 kb) as being essential for activation, and we have shown that the NF kappa B, SP1, and TATA box motifs in the human immunodeficiency virus LTR are all required for full induction of the promoter by the HHV-6-encoded transactivator.